Comparative Study of Trichoderma-infused Compost on Growth and Yield of Chili Plants - Ong, Ghim Hock; Subramaniam, G.; Tan, A.L. (Global Science Publications, 2015)
Chili Kulai (Capsicum annuum) is an important agricultural crop in many countries due to its economic importance, nutritional and medicinal value. The aim of this study was to determine the effect of Trichoderma infused compost on the growth and yield of chili plants. Two treatments were carried out, which were chemical fertilizer (CF) and Trichoderma-infused compost (TC). Plants without any treatment were included as controls in this study. Three replicates were carried out for each treatment. The growth parameters including plant height and the number of branches were measured. The yield parameters observed were in terms of number of chilies produced, weight of chilies, length of chilies, percentage of ripened chilies and fungal-infected chilies. TC and CF showed comparable results in relation to all the parameters observed. The plants treated with TC grew as well as CF treated plants. The plants in TC treated group could also produce comparable yield of chilies as CF treated plants. The results from this study indicate that Trichoderma infused compost is a suitable and effective replacement for chemical fertilizers for the growth and production of chilies.